Root-cause regulation protecting work and workers in the twenty-first century - Piore, Michael J. (Harvard University Press, 2018)
Why does the United States assign responsibility for different aspects of labor and employment law (e.g., wages and hours, safety and health, collective bargaining, discrimination, etc.) to different agencies, when France, Spain, and their former colonies assign all aspects of labor and employment law to a single agency? Does the US approach, which essentially reduces to "one inspector per law," perform better or worse than the "Latin" model, which implies "one inspector per firm?" And what are the implications for the division of labor in the public sector more generally? Root-Cause Regulation addresses these questions by comparing the evolution of labor market regulation in developed and developing countries over the course of the past century. The results speak not only to the protection of work and workers in the twenty-first century but to the organization of the public sector more generally.--